THE INFLUENCE OF PERSONAL HYGIENE PUZZLE MEDIA WASHING HANDS WITH SOAP ON STUDENTS' KNOWLEDGE OF SDN 6 PARAKAN KAUMAN TEMANGGUNG - Prieta Wahyu Perwitasari; Omega DR Year (International Journal Of Health Science, 2023)
Background : Diarrhea is still a global problem today and is still a serious concern from various countries. This was reported in the World Health Organization (WHO) which describes cases of diarrhea in the world in 2017 stating that there are nearly 1.7 billion cases of diarrheal disease that occur in children with 525,000 deaths every year worldwide. The occurrence of diarrhea will cause children to lose the nutrients that children need for growth and development, so diarrhea is the main cause of malnutrition in school-age children. The World Health Organization (WHO) states that washing hands with soap can reduce diarrhea rates by up to 47%. Purpose : Analyzing the effect of personal hygiene puzzle media washing hands with soap on students' knowledge of SDN 6 Parakan Kauman Temanggung Research Method: Pre-experimental design with one group pre-post test. The sampling technique used total sampling, namely 29 students at SDN 6 Parakan. Data analysis with Wilcoxon test Research result : The majority of respondents' knowledge before being given puzzle media was in the good category, namely 15 (51.7%) respondents, while after giving puzzle media, the majority were good, namely 22 (75.9%) respondents. The results of the Wilcoxon test found a p value of 0.000 <0.05 meaning that there was an effect of giving hand washing personal hygiene puzzle media with knowledge to elementary school students in Temanggung Conclusions and recommendations : Giving puzzle media can affect students' knowledge about personal hygiene hand washing. It is hoped that the hand washing puzzle media can be used as a medium in increasing student knowledge